Executive Function and Education - Mariëtte Huizinga (Frontiers Research Topics, 2018)
Executive function is an umbrella term for various cognitive processes that are central to goal-directed behavior, thoughts, and emotions. These processes are especially important in novel or demanding situations, which require a rapid and flexible adjustment of behavior to the changing demands of the environment. The development of executive function relies on the maturation of associated brain regions as well as on stimulation in the child's social contexts, especially the home and school. Over the past decade, the term executive function has become a buzzword in the field of education as both researchers and educators underscore the importance of skills like goal setting, planning, and organizing in academic success. Accordingly, in initiating this Research Topic and eBook our goal was to provide a forum for state-of-the-art theoretical and empirical work on this that both facilitates communication among researchers from diverse fields and provides a theoretically sound source of information for educators. The contributors to this volume, who hail from several different countries in Europe and North America, have certainly accomplished this goal in their nuanced and cutting-edge depictions of the complex links among various executive function components and educational success.